Expansion of tree-shrub vegetation in upper-montane open areas adjacent to forest fragments, in “planalto sul catarinense” region Expansão da vegetação arbustivo-arbórea em áreas abertas alto-montanas adjacentes a fragmentos florestais, no planalto sul catarinense - Dallabrida J.P.* (2019)
© 2019, Universidade Federal de Santa Maria. All rights reserved.The study aimed to understand the dynamic patterns of natural regeneration of shrub-tree species and determine whether these patterns are influenced by environmental variables, in three open areas in natural regeneration (diameter at breast height < 5 cm), in contact to upper-montane Araucaria Forest fragments, located in the Southern Plateau of Santa Catarina state. Three 20x100 m transects, subdivided into sub-plots of 10x10 m, were installed in each area, perpendicular to the edge of the fragments with their length covering the grassland area. All shrub-tree regenerating individuals greater than or equal to 20 cm height were sampled. In each sub-plot, the environmental data were collected: soil physico-chemical properties, the degree of soil compaction and the altimetric quota. One year after the first inventory, the dynamics rates were obtained for the three community and populations, and the found patterns related to environmental variables. The data were analyzed through Kruskal-Wallis tests, multiple comparison tests, chi-square test, applied to a contingency table, Principal Component Analysis (PCA) and linear mixed models. The results demonstrated that during the evaluated period, the natural regeneration process of the shrub-tree component is found in an early stage and it was characterized by abundance increment, richness stability, spatial independency between mortality and recruitment, and recruitment limitation in function of low soil natural fertility and high Al availability.